A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand - Lheknim, Vachira; Ng, Peter K. L. (Zootaxa, 2016)
A new species of terrestrial potamid crab, Terrapotamon longitarsus, is described from limestone hills in Satun Province in southern Thailand. It is easily distinguished from other Terrapotamon species by its conspicuously long ambulatory legs (all congeners have proportionately short legs), relatively smooth dorsal surface of carapace, transversely narrow male thoracic sternites 1–4, and a characteristically structured male first gonopod.